2001
DOI: 10.1177/0164027501231005
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Patient Racial Matching, Effectiveness of Care, Use of Services, and Patient Satisfaction

Abstract: The authors examined how racial matching between older patients and physicians relates to effectiveness of care, use of services, and satisfaction with care. In this cross-sectional, community-based cohort study, 2,867 elderly African American and White North Carolina residents with regular physicians were interviewed and screened for hypertension (HBP). African Americans were more likely than Whites to be told they had HBP, to receive HBP medication, and to take it regardless of their physician’s race. White … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Contrary to conventional belief, race does not appear to play a significant part in determining patient satisfaction in older people (Jackson & George, 1998); moreover, there is evidence to suggest that black elders matched with black physicians are the least likely to be very satisfied (Howard et al, 2001).…”
Section: Background Characteristicsmentioning
confidence: 78%
See 1 more Smart Citation
“…Contrary to conventional belief, race does not appear to play a significant part in determining patient satisfaction in older people (Jackson & George, 1998); moreover, there is evidence to suggest that black elders matched with black physicians are the least likely to be very satisfied (Howard et al, 2001).…”
Section: Background Characteristicsmentioning
confidence: 78%
“…Of these few investigations of health service satisfaction involving elderly patients, most have focused on their perceptions of physician services rendered in outpatient settings (Adler, 1995;Brand, Cronin, & Routledge, 1997;Burton, Weiner, & Folkemer, 2001;Dickens et al, 1993;Howard et al, 2001;Jackson & George, 1998;Linn, Linn, & Stein, 1982;Scotti & Dolinsky, 1997;Shank et al 1992). To date, research that has focused exclusively on the determinants of hospital service satisfaction among elderly inpatients has been more limited (Breemhaar, Visser, & Kleijnen, 1990;Cohen, 1996;Jaipaul & Rosenthal, 2003;Jones & Lester, 2003;Scotti & Stinerock, 2003).…”
Section: Research Findingsmentioning
confidence: 99%
“…To date, four studies have assessed the effect of race concordance on medication adherence (24,27,28, 41). Using data from the Piedmont Health Survey of the Elderly, Howard et al (41) and Konrad et al (28) found that race concordance had little effect on whether elderly hypertensive patients take their antihypertensive medications. Rather, black patients overall were more likely to be prescribed antihypertensive medications and report taking them as compared to their white counterparts, regardless of provider race (38).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients whose primary physicians are of a different race/ethnicity, patients who are of the same racial or ethnic group as their physicians are more likely to use needed health services, are less likely to postpone or delay seeking care and report a higher volume of use of health services 24,25. Other studies have found that language concordance and interpreter use positively affects patients’ perceived understanding of their disease and is positively associated with a range of health comes26,27.…”
Section: Introductionmentioning
confidence: 99%